Cobalt phosphide-porous carbon nanoflower composite material and preparation method thereof, lithium ion battery and electric equipment

By using cobalt phosphide-porous carbon nanoflower composite material as the negative electrode material for lithium-ion batteries, the problems of low capacity and poor conductivity of the negative electrode material in the prior art are solved, and battery performance with high energy density and good cycle stability are achieved.

CN119637820APending Publication Date: 2025-03-18XICHANG EPNO NEW ENERGY TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954996.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The theoretical capacity of graphite-based anode materials of existing lithium-ion batteries is low and cannot meet the needs of high energy density. At the same time, transition metal phosphides, as negative electrode materials, have problems such as poor conductivity and fast capacity decay.

Method used

Cobalt phosphide-porous carbon nanoflower composite material is used as the negative electrode material to prepare cobalt hydroxide nanosheets by hydrothermal method, and convert it into cobalt phosphide-porous carbon nanoflower composite material through calcination process to improve the conductivity and structural stability of the material.

Benefits of technology

It achieves high capacity, good cycle stability and long service life of lithium-ion batteries, and improves the energy density and power density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637820A_ABST
    Figure CN119637820A_ABST
Patent Text Reader

Abstract

The invention provides a cobalt phosphide-porous carbon nanoflower composite material and a preparation method thereof, a lithium ion battery and electric equipment, and relates to the field of lithium ion batteries. The preparation method comprises the following steps: carrying out first mixing on cobalt salt, hexamethylenetetramine, water and ethylene glycol, and carrying out hydrothermal reaction to obtain cobalt hydroxide nanosheets; carrying out second mixing on the cobalt hydroxide nanosheets and sodium citrate, and carrying out first calcination on the obtained mixture in an inert atmosphere to obtain a first calcined product; and carrying out third mixing on the first calcined product and red phosphorus, and carrying out second calcining on the obtained mixture in an inert atmosphere to obtain the cobalt phosphide-porous carbon nanoflower composite material. Cobalt hydroxide nanosheets are prepared by adopting a simple hydrothermal method, then the cobalt hydroxide nanosheets are respectively calcined with sodium citrate and red phosphorus to prepare the cobalt phosphide-porous carbon nanoflower composite material, the prepared cobalt phosphide is small in particle size, the ion diffusion length can be shortened, and rapid transmission can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a cobalt phosphide-porous carbon nanoflower composite material and a preparation method thereof, a lithium-ion battery and electrical equipment. Background Art

[0002] With the rapid development of electric vehicles and 3C products, people are increasingly in need of energy storage batteries with high energy and high power density. Although lithium-ion batteries have excellent electrochemical properties, the theoretical capacity of their graphite-based negative electrode materials is only 372 mAhg -1 , has gradually been unable to meet people's demand for high energy density. Therefore, finding new negative electrode materials has become an effective way to improve lithium-ion batteries.

[0003] Transition metal phosphides have attracted much attention due to their high specific capacity, good wear resistance and corrosion resistance, as well as excellent catalytic activity and stability in alkaline media. At the same time, transition metal phosphides also have large theoretical capacity and weak MS bonds, as well as a variety of possible valence states, and are considered to be one of the candidates for new high-performance lithium battery negative electrode materials.

[0004] However, transition metal phosphides are semiconductor materials with poor conductivity. When cobalt phosphide is used as the negative electrode material, during the insertion and extraction of lithium ions, the capacity decays rapidly due to the partial dissolution and volume change of the polyphosphide intermediates, which seriously hinders its practical application.

[0005] Studies have shown that reducing the size of cobalt phosphide helps shorten the diffusion path of ions and electrons and improve the rate performance of lithium-ion batteries. At the same time, constructing cobalt phosphide / carbonaceous material nanocomposites can improve the conductivity of the material and buffer the volume changes during charge and discharge. However, due to the weak chemical bond between the active nanoparticles and the carbonaceous material, the cobalt phosphide nanoparticles are prone to move and agglomerate during the cycle, resulting in the crushing of the active material and reducing the cycle stability of the material. Therefore, when these nanocomposites are used as negative electrode materials for lithium-ion batteries, they often experience severe capacity decay during long-term cycles. Summary of the invention

[0006] The purpose of this application is to provide a cobalt phosphide-porous carbon nanoflower composite material and a preparation method thereof, a lithium ion battery and an electrical device to solve the above-mentioned problems.

[0007] To achieve the above objectives, the present application provides a first aspect of a method for preparing a cobalt phosphide-porous carbon nanoflower composite material, comprising:

[0008] The cobalt salt, hexamethylenetetramine, water and ethylene glycol are first mixed and subjected to a hydrothermal reaction to obtain cobalt hydroxide nanosheets;

[0009] The cobalt hydroxide nanosheets and sodium citrate are mixed for a second time, and the obtained mixture is calcined for a first time under an inert atmosphere to obtain a first calcined product;

[0010] The first calcined product and red phosphorus are mixed for a third time, and the obtained mixture is calcined for a second time under an inert atmosphere to obtain a cobalt phosphide-porous carbon nanoflower composite material.

[0011] Optionally, the preparation method of the cobalt phosphide-porous carbon nanoflower composite material meets at least one of the following conditions:

[0012] A. The cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt nitrate, cobalt sulfate, cobalt acetate, and cobalt hydrochloride;

[0013] B. The pH value of the mixture subjected to the first calcination is 8.5-9.0.

[0014] Optionally, the method for preparing the cobalt phosphide-porous carbon nanoflower composite material satisfies at least one of the following conditions:

[0015] A. the molar ratio of the cobalt salt to the hexamethylenetetramine is 1:3.7-4;

[0016] B. The mass ratio of water to ethylene glycol is 1:1.4-1.6.

[0017] Optionally, the method for preparing the cobalt phosphide-porous carbon nanoflower composite material satisfies at least one of the following conditions:

[0018] A. The molar ratio of the cobalt hydroxide nanosheets to the sodium citrate is 1:1.7-2.2;

[0019] B. The molar ratio of the first calcined product to the red phosphorus is 1:0.9-1.05.

[0020] Optionally, the temperature of the hydrothermal reaction is 120°C-130°C, and the time is 5h-6h.

[0021] Optionally, the endpoint temperature of the first calcination is 650°C-750°C, the time is 1.5h-2h, and the heating rate is 5°C / min-8°C / min.

[0022] Optionally, the end point temperature of the second calcination is 850°C-900°C, the time is 1.5-2h, and the heating rate is 5°C / min-8°C / min.

[0023] The second aspect of the present application provides a cobalt phosphide-porous carbon nanoflower composite material, which is prepared by the preparation method of the cobalt phosphide-porous carbon nanoflower composite material.

[0024] The third aspect of the present application provides a lithium-ion battery, comprising the cobalt phosphide-porous carbon nanoflower composite material.

[0025] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.

[0026] Compared with the prior art, the beneficial effects of this application include:

[0027] The preparation method of the cobalt phosphide-porous carbon nanoflower composite material provided in the present application adopts a simple hydrothermal method to prepare cobalt hydroxide nanosheets, and then prepares the cobalt phosphide-porous carbon nanoflower composite material by calcining with sodium citrate and red phosphorus respectively. The prepared cobalt phosphide has a small particle size, which can shorten the ion diffusion length and achieve rapid transmission.

[0028] The cobalt phosphide-porous carbon nanoflower composite material provided in the present application has a reasonable structural design, and the two-dimensional carbon nanosheet layer can provide a rich specific surface area and high conductivity. The heterogeneous structure formed by the cobalt phosphide nanoparticles coated by the two-dimensional carbon nanosheet layer can provide a large number of active sites, while improving its structural stability, so that it has good cycle stability and excellent lithium storage performance.

[0029] The lithium-ion battery and electrical equipment provided by the present application have high capacity, good cycle stability and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0031] Figure 1 This is a SEM image of the cobalt phosphide-porous carbon nanoflower composite material prepared in Example 1;

[0032] Figure 2 This is a test curve of the electrochemical performance of the button cell prepared in Example 1. DETAILED DESCRIPTION

[0033] As used herein:

[0034] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0035] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0036] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0037] In these examples, parts and percentages are by mass unless otherwise indicated.

[0038] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0039] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0040] The first aspect of the present application provides a method for preparing a cobalt phosphide-porous carbon nanoflower composite material, comprising:

[0041] The cobalt salt, hexamethylenetetramine, water and ethylene glycol are first mixed and subjected to a hydrothermal reaction to obtain cobalt hydroxide nanosheets;

[0042] It should be noted that hexamethylenetetramine, as a template, helps to form a specific microstructure. The molecular structure of hexamethylenetetramine can guide the growth direction and morphology of cobalt hydroxide materials, help to generate two-dimensional cobalt hydroxide nanosheets, and hexamethylenetetramine generates OH by hydrolysis.- , providing an alkaline environment for the solution, so that cobalt hydroxide nanosheets can be better formed. The specific reaction is as follows:

[0043] (CH2)6N4+6H2O→6HCHO+4NH3;

[0044] NH3+H2O→NH4 + +OH - ;

[0045] The cobalt hydroxide nanosheets and sodium citrate are mixed for a second time, and the obtained mixture is calcined for a first time under an inert atmosphere to obtain a first calcined product;

[0046] It should be noted that sodium citrate is easy to prepare porous carbon materials as a carbon source. When sodium citrate is carbonized, it is converted into a cross-linked carbon nanosheet structure, and the sodium carbonate produced by calcination acts as a foaming agent for the pore structure. At this time, a large amount of gas is generated, and the gas escapes from the inside to the outside to generate new pores, and finally forms a porous structure carbon. The porous carbon has a high specific surface area, high conductivity, and high stability. In addition, sodium citrate is used as a carbon source and basically no impurity products are generated;

[0047] The first calcined product and red phosphorus are mixed for a third time, and the obtained mixture is calcined for a second time under an inert atmosphere to obtain a cobalt phosphide-porous carbon nanoflower composite material.

[0048] It should be noted that the cobalt hydroxide nanosheet precursor is converted into cobalt oxide nanoparticles. After a series of complex reaction processes during high-temperature calcination, these cobalt oxide nanoparticles are fixed and encapsulated in carbon materials, which is conducive to limiting the range of activity of cobalt oxide nanoparticles in composite materials. In addition, the cobalt oxide nanoparticles in the first calcination product have strong reactivity, so after mixing them with phosphorus powder, in-situ phosphating is achieved at 850-900℃.

[0049] It should also be noted that the use of synthesized cobalt hydroxide nanosheets as the cobalt source can control the dispersion and size of cobalt phosphide nanoparticles, ensuring a smaller volume expansion rate during long-term cycles; and the in-situ phosphating of cobalt trioxide nanoparticles can ensure that their extreme positions obtain a stable structure.

[0050] On the one hand, the cobalt phosphide nanoparticles wrapped by the carbon nanostructure in the prepared cobalt phosphide-porous carbon nanoflower composite material are separated from each other, preventing serious particle agglomeration during the reaction and avoiding direct contact between the active nanoparticles and the electrolyte. On the other hand, the small-diameter cobalt phosphide particles and the conductive ultra-thin carbon nanosheet structure can obtain a large specific surface area, thereby increasing the utilization rate of the active material, and this nanostructure can effectively shorten the diffusion path of lithium ions. After the in-situ catalytic action of the metal particles, some amorphous carbon in the material is graphitized, constructing a fast electron transfer path, thereby realizing fast charge transfer, thereby further promoting the contribution of pseudocapacitive behavior to high scan rate lithium storage performance.

[0051] In some embodiments, the method for preparing the cobalt phosphide-porous carbon nanoflower composite material satisfies at least one of the following conditions:

[0052] A. The cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt nitrate, cobalt sulfate, cobalt acetate, and cobalt hydrochloride;

[0053] B. The pH value of the mixture subjected to the first calcination is 8.5-9.0.

[0054] Optionally, the pH value of the mixture subjected to the first calcination may be 8.5, 8.6, 8.7, 8.8, 8.9, 9 or any value between 8.5 and 9.0.

[0055] In some embodiments, the method for preparing the cobalt phosphide-porous carbon nanoflower composite material satisfies at least one of the following conditions:

[0056] A. the molar ratio of the cobalt salt to the hexamethylenetetramine is 1:3.7-4;

[0057] Optionally, the molar ratio of the cobalt salt to hexamethylenetetramine may be 1:3.7, 1:3.8, 1:3.9, 1:4 or any value between 1:3.7 and 4;

[0058] B. The mass ratio of water to ethylene glycol is 1:1.4-1.6.

[0059] Optionally, the mass ratio of water to ethylene glycol can be 1:1.4, 1:1.5, 1:1.6 or any value between 1:1.4 and 1.6.

[0060] In some embodiments, the method for preparing the cobalt phosphide-porous carbon nanoflower composite material satisfies at least one of the following conditions:

[0061] A. The molar ratio of the cobalt hydroxide nanosheets to the sodium citrate is 1:1.7-2.2;

[0062] Optionally, the molar ratio of cobalt hydroxide nanosheets to sodium citrate can be 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2 or any value between 1:1.7 and 2.2;

[0063] It should be noted that the molar ratio of cobalt hydroxide nanosheets and sodium citrate determines the final morphology and performance of porous carbon nanoflowers. When the amount of sodium citrate is too little, the coating is incomplete and affects the ion transmission effect, while when the amount of sodium citrate is too much, it will affect the formation of porous carbon.

[0064] B. The molar ratio of the first calcined product to the red phosphorus is 1:0.9-1.05.

[0065] Optionally, the molar ratio of the first calcined product to the red phosphorus may be 1:0.9, 1:0.95, 1:1, 1:1.05 or any value between 1:0.9-1.05.

[0066] In some embodiments, the temperature of the hydrothermal reaction is 120° C.-130° C., and the time is 5 h-6 h.

[0067] Optionally, the temperature of the hydrothermal reaction can be 120°C, 125°C, 130°C or any value between 120°C and 130°C, and the time can be 5h, 5.5h, 6h or any value between 5h and 6h.

[0068] In some embodiments, the endpoint temperature of the first calcination is 650°C-750°C, the time is 1.5h-2h, and the heating rate is 5°C / min-8°C / min.

[0069] Optionally, the endpoint temperature of the first calcination can be 650°C, 700°C, 750°C or any value between 650°C and 750°C, the time can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or any value between 1.5h and 2h, and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min or any value between 5°C / min and 8°C / min.

[0070] In some embodiments, the end point temperature of the second calcination is 850-900°C, the time is 1.5-2h, and the heating rate is 5-8°C / min.

[0071] Optionally, the endpoint temperature of the second calcination can be 850°C, 860°C, 870°C, 880°C, 890°C, 900°C or any value between 850-900°C, the time can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or any value between 1.5h-2h, and the heating rate can be 5°C / min, 6°C / min, 7°C / min, 8°C / min or any value between 5°C / min-8°C / min.

[0072] The second aspect of the present application provides a cobalt phosphide-porous carbon nanoflower composite material, which is prepared by the preparation method of the cobalt phosphide-porous carbon nanoflower composite material.

[0073] The third aspect of the present application provides a lithium-ion battery, comprising the cobalt phosphide-porous carbon nanoflower composite material.

[0074] A fourth aspect of the present application provides an electrical device comprising the lithium-ion battery.

[0075] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0076] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0077] Example 1

[0078] This embodiment provides a cobalt phosphide-porous carbon nanoflower composite material and a preparation method thereof, and the specific steps are as follows:

[0079] S1: 1 mmol of cobalt nitrate hexahydrate, 4 mmol of hexamethylenetetramine, 10 mL of deionized water and 15 mL of ethylene glycol were added to a container, stirred at a speed of 1200 rpm / min for 20 minutes to completely dissolve the solid, and the uniformly dispersed solution was transferred to a high-pressure reactor, kept at 130°C for 6 hours, and after cooling to room temperature, filtered and washed three times with deionized water and ethanol respectively to obtain precursor cobalt hydroxide nanosheets;

[0080] S2: Grind and mix cobalt hydroxide nanosheets and sodium citrate at a molar ratio of 1:2, place the mixture in a muffle furnace, heat it at a rate of 5°C / min, and calcine it at 700°C for 2 hours in an argon atmosphere to obtain a composite material of cobalt oxide nanoparticles and two-dimensional porous carbon nanosheets;

[0081] S3: The above composite material and red phosphorus powder are mixed evenly in a molar ratio of 1:1, placed in a muffle furnace with an argon atmosphere, heated to 900°C at 5°C / min and calcined for 2 hours, while maintaining the argon atmosphere and cooling to room temperature to obtain a cobalt phosphide-porous carbon nanoflower composite material.

[0082] The final product, cobalt phosphide-porous carbon nanoflower composite material, was used as the negative electrode to prepare button-type batteries to test the electrical performance. -1 The first coulombic efficiency is 65.68% at a current density of 1.37 W, and the first reversible specific capacity is 807.16 mAh g -1 The reversible specific capacity after 100 cycles can be maintained at 806.11 mAh g -1 .

[0083] The SEM images of the cobalt phosphide-porous carbon nanoflower composite material are shown in Figure 2. Figure 1 shown.

[0084] Example 2

[0085] The difference from Example 1 is that the molar ratio of cobalt hydroxide nanosheets to sodium citrate is 1:1.7.

[0086] Example 3

[0087] The difference from Example 1 is that the molar ratio of cobalt hydroxide nanosheets to sodium citrate is 1:2.2.

[0088] Comparative Example 1

[0089] The difference from Example 1 is that the molar ratio of cobalt hydroxide nanosheets to sodium citrate is 1:1.

[0090] Comparative Example 2

[0091] The difference from Example 1 is that the molar ratio of cobalt hydroxide nanosheets to sodium citrate is 1:3.

[0092] Comparative Example 3

[0093] This comparative example provides a cobalt phosphide-porous carbon nanoflower composite material and a preparation method thereof, and the specific steps are as follows:

[0094] S1: 1 mmol of cobalt nitrate hexahydrate, 4 mmol of hexamethylenetetramine, 10 mL of deionized water and 15 mL of ethylene glycol were added to a container, stirred at a speed of 1200 rpm / min for 20 minutes to completely dissolve the solid, and the uniformly dispersed solution was transferred to a high-pressure reactor, kept at 130°C for 6 hours, and after cooling to room temperature, filtered and washed three times with deionized water and ethanol respectively to obtain precursor cobalt hydroxide nanosheets;

[0095] S2: placing the cobalt hydroxide nanosheets in a muffle furnace, heating at a rate of 5°C / min, and calcining at 900°C for 2 hours in an argon atmosphere to obtain cobalt trioxide nanoparticles;

[0096] S3: The above-mentioned cobalt oxide nanoparticles and red phosphorus powder are mixed evenly in a molar ratio of 1:1, put into a muffle furnace with an argon atmosphere, heat to 900°C at 5°C / min and calcine for 2 hours, while maintaining the argon atmosphere and cooling to room temperature to obtain a cobalt phosphide nanoflower material.

[0097] Comparative Example 4

[0098] This embodiment provides a cobalt phosphide-porous carbon composite material and a preparation method thereof, and the specific steps are as follows:

[0099] S1: 1 mmol of cobalt nitrate hexahydrate and 10 mL of deionized water were added to a container, and stirred at a speed of 1200 rpm / min for 20 minutes to completely dissolve the solid. The mixture was stirred continuously and a suitable amount of ammonia water was added to adjust the pH to 8.5 to produce a precipitate. The mixture was filtered and washed three times with deionized water, and dried at 80°C for 6 hours to obtain precursor cobalt hydroxide particles.

[0100] S2: Grind and mix cobalt hydroxide particles and sodium citrate at a molar ratio of 1:1, place the mixture in a muffle furnace, heat it at a rate of 5°C / min, and calcine it at 700°C for 2 hours in an argon atmosphere to obtain cobalt oxide particles and a porous carbon composite material;

[0101] S3: The above composite material and red phosphorus powder are mixed evenly in a molar ratio of 1:1, placed in a muffle furnace with an argon atmosphere, heated to 900°C at 5°C / min, and calcined for 2 hours, while maintaining the argon atmosphere and cooling to room temperature to obtain a cobalt phosphide-porous carbon composite material.

[0102] It can be seen from this comparative example that in the process of preparing cobalt hydroxide, hexamethylenetetramine is replaced with ammonia water. Ammonia water provides an alkaline environment but has no guiding growth effect. This shows that not any compound that can provide an alkaline environment can prepare the precursor cobalt hydroxide nanosheets, thereby preparing the cobalt phosphide-porous carbon nanoflower composite material.

[0103] Comparative Example 5

[0104] This embodiment provides a cobalt phosphide-carbon nanoflower composite material and a preparation method thereof, and the specific steps are as follows:

[0105] S1: 1 mmol of cobalt nitrate hexahydrate, 4 mmol of hexamethylenetetramine, 10 mL of deionized water and 15 mL of ethylene glycol were added to a container, stirred at a speed of 1200 rpm / min for 20 minutes to completely dissolve the solid, and the uniformly dispersed solution was transferred to a high-pressure reactor, kept at 130°C for 6 hours, and after cooling to room temperature, filtered and washed three times with deionized water and ethanol respectively to obtain precursor cobalt hydroxide nanosheets;

[0106] S2: Add asphalt to an ethanol solution and stir to completely dissolve it, add cobalt hydroxide nanosheets to the solution and stir to mix them evenly, wherein the mass ratio of cobalt hydroxide nanosheets to asphalt is 1:1, and then place in an oven at 60°C for 12 hours for drying, place the dried mixture in a muffle furnace, heat at a rate of 5°C / min, and calcine at 450°C for 2 hours in an argon atmosphere to obtain a composite material of cobalt oxide nanoparticles and carbon nanosheets;

[0107] S3: The above composite material and red phosphorus powder are mixed evenly in a molar ratio of 1:1, placed in a muffle furnace with an argon atmosphere, heated to 900°C at 5°C / min and calcined for 2 hours, while maintaining the argon atmosphere and cooling to room temperature to obtain a cobalt phosphide-carbon nanoflower composite material.

[0108] Comparative Example 6

[0109] The difference from Example 1 is that the molar ratio of cobalt tetroxide particles, porous carbon composite material and red phosphorus powder is 1:0.5.

[0110] The materials obtained in the above Examples 1-3 and Comparative Examples 1-6 were used as negative electrode materials to prepare button batteries, wherein the preparation method of the button batteries is as follows:

[0111] The active material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone was added as a solvent to form a uniform slurry. The slurry was then evenly coated on a copper foil with a diameter of 16 mm. The copper foil coated with the active material was placed in a vacuum drying oven at 110°C for 12 hours. After cooling to room temperature, the electrode material was rolled using a roller press (pressure 10 MPa).

[0112] The half-cell was assembled in an Ar-protected glove box using a CR2430 button cell. The assembly sequence was: positive electrode shell - lithium sheet - diaphragm - electrolyte - active material - gasket - spring - negative electrode shell, where the electrolyte was 1 mol L -1A mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (EMC) of LiPF6 is prepared in a volume ratio of 1:1:1. The half-cell is then sealed and formed, completing the assembly. The assembled half-cell is left to stand for 24 hours to allow the battery to reach a stable state.

[0113] The prepared button cell was subjected to electrochemical performance tests, including -1 The first coulombic efficiency, the first reversible specific capacity and the reversible specific capacity after 100 cycles at a current density of , and the specific test results are shown in Table 1.

[0114] The electrochemical performance test curve of the button cell prepared in Example 1 is as follows: Figure 2 shown.

[0115] Table 1 Electrochemical performance test

[0116]

[0117] analyze:

[0118] From the data comparison of Example 1-3 and Comparative Example 1-5 in Table 1, it can be seen that the electrochemical performance of Example 1-3 is better than that of Comparative Example 1-5. This shows that Example 1-3 can significantly improve the electrochemical performance and the cycle stability of the negative electrode material by utilizing the synergistic effect of the cobalt phosphide-porous carbon nanoflower composite material structure, thereby making the lithium-ion battery have both high charge capacity and first-cycle coulomb efficiency, and exhibit excellent stability and lithium storage performance.

[0119] From the comparison of the data of Example 1 and Comparative Example 1, it can be seen that due to the small amount of sodium citrate added in Comparative Example 1, the lack of porous carbon source in the final product leads to an incomplete carbon nanoflower structure, which cannot inhibit the expansion of the material during the charge and discharge cycle. At the same time, there is no stable transmission channel for lithium ions, which will cause the nanoflower structure to break after multiple cycles, affecting its cycle stability.

[0120] From the comparison of the data of Example 1 and Comparative Example 2, it can be seen that due to the large amount of sodium citrate added in Comparative Example 1, during high-temperature carbonization, the external material will block the discharge of gas during internal carbonization to form a structure with a hollow outside and a solid inside, thereby blocking the transmission channel of lithium ions and affecting the electrical properties of the material.

[0121] Comparative Example 3 is a cobalt phosphide material without the introduction of porous carbon containing sodium citrate. Compared with the data of Example 1, the absence of carbon material cannot effectively prevent the aggregation and volume change of cobalt phosphide particles during the charge and discharge process, thereby aggravating the expansion in the electrochemical reaction until the structure is broken and the electrical performance drops sharply.

[0122] From the comparison of the data of Example 1 and Comparative Example 4, it can be seen that due to the lack of hexamethylenetetramine in the reaction, the precursor cobalt hydroxide does not grow in a directional manner into a nanoflower structure, but forms a lamellar structure with a larger particle size. The lamellar structure is not conducive to the transmission of ions. At the same time, the larger particle size will aggravate the expansion during the charge and discharge process, affecting its electrical properties.

[0123] Comparative Example 5 introduces the carbon source from asphalt. Compared with the data of Example 1, it can be seen that since the asphalt does not have the characteristics of porous carbon after carbonization, the conductivity of the material is poor, and it will affect the uniform distribution of the carbon layer and cause the agglomeration of cobalt phosphide nanoparticles, which is not conducive to the transmission of ions in the material. However, Comparative Example 5 has a nanoflower structure and introduces a carbon layer, which is more complete and stable than Comparative Examples 3 and 4, so the cycle life is better than Comparative Examples 3 and 4.

[0124] From the comparison of the data of Examples 1-3 and Comparative Example 6, it can be seen that the proportion of red phosphorus in Comparative Example 6 is relatively small, the cobalt tetroxide in the precursor reacts incompletely with the red phosphorus, and the product may be a mixed material of cobalt tetroxide, cobalt phosphide, and porous carbon. The incomplete reaction products will cause obstacles in the process of ion and electron transmission, seriously affecting the electrical properties of the material, resulting in poor first coulomb efficiency and cycle stability.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0126] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a cobalt phosphide-porous carbon nanoflower composite material, characterized in that: include: The cobalt salt, hexamethylenetetramine, water and ethylene glycol are first mixed and subjected to a hydrothermal reaction to obtain cobalt hydroxide nanosheets; The cobalt hydroxide nanosheets and sodium citrate are mixed for a second time, and the obtained mixture is calcined for a first time under an inert atmosphere to obtain a first calcined product; The first calcined product and red phosphorus are mixed for a third time, and the obtained mixture is calcined for a second time under an inert atmosphere to obtain a cobalt phosphide-porous carbon nanoflower composite material.

2. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to claim 1, characterized in that: At least one of the following conditions is met: A. The cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt nitrate, cobalt sulfate, cobalt acetate, and cobalt hydrochloride; B. The pH value of the mixture subjected to the first calcination is 8.5-9.

0.

3. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to claim 1, characterized in that: At least one of the following conditions is met: A. the molar ratio of the cobalt salt to the hexamethylenetetramine is 1:3.7-4.0; B. The mass ratio of water to ethylene glycol is 1:1.4-1.

6.

4. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to claim 1, characterized in that: At least one of the following conditions is met: A. The molar ratio of the cobalt hydroxide nanosheets to the sodium citrate is 1:1.7-2.2; B. The molar ratio of the first calcined product to the red phosphorus is 1:0.9-1.

05.

5. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120° C.-130° C., and the time is 5 h-6 h.

6. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to claim 1, characterized in that: The endpoint temperature of the first calcination is 650°C-750°C, the time is 1.5-2h, and the heating rate is 5°C / min-8°C / min.

7. The method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to any one of claims 1 to 6, characterized in that: The end point temperature of the second calcination is 800°C-900°C, the time is 1.5h-2h, and the heating rate is 5°C / min-8°C / min.

8. A cobalt phosphide-porous carbon nanoflower composite material, characterized in that: The composite material is prepared by the method for preparing the cobalt phosphide-porous carbon nanoflower composite material according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: It includes the cobalt phosphide-porous carbon nanoflower composite material as described in claim 8.

10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.